Analysis of the Digital Citizenship Practices among University Students in Pakistan - Bakht Jamal, Syed Asad Abbas Rizvi (PJDOL, 2023)
This paper intended to analyze the practices of digital citizenship among university student in Pakistan. The quantitative descriptive survey research design was adopted for this study. The population of the study was 800 students of BS (Education) program in ten public sector universities in Punjab, Pakistan. Simple random sampling technique was used for the selection of sample. T